Understanding the Burden of Atopic Dermatitis in Africa and the Middle East - Khalid Abdullah Mohammad Al-Afif; Mohamad Ali Buraik; Joerg Buddenkotte; Mohamed Mounir; Robert Gerber; Haytham Mohamed Ahmed; Anna M. Tallman; Martin Steinhoff (Adis, Springer Healthcare, 2019)
Abstract Atopic dermatitis (AD) is a common inflammatory skin disease characterized by intensely pruritic lesions. The prevalence of atopic dermatitis is increasing in developing regions, including Africa and the Middle East. However, these regions are underrepresented in the dermatology literature, and a better understanding of the growing burden of atopic dermatitis in Africa and the Middle East is necessary. Herein, we summarize current knowledge on atopic dermatitis epidemiology, disease burden, and treatment options in Africa and the Middle East, highlighting the unmet needs of patients in these regions. With these needs in mind, we provide clinical recommendations for appropriate management of atopic dermatitis in Africa and the Middle East. Funding Pfizer Inc. Plain Language Summary Plain language summary available for this article.